Abnormal haem biosynthesis in the chronic anaemia of rheumatoid arthritis. - Houston, T (1994)
OBJECTIVES--The chronic microcytic anaemia of rheumatoid arthritis (RA) occurs despite the presence of adequate reticulo-endothelial iron stores. The red cell microcytosis is evidence of impaired haemoglobin production. This study has examined possible abnormalities of erythroid haem biosynthesis that may contribute to the anaemia. METHODS--5-Aminolaevulinate (ALA) synthase and ferrochelatase activities were assayed in whole bone marrow and in purified erythroblasts from patients with RA and in control subjects. All patients were iron replete with demonstrable iron in the bone marrow. RESULTS--ALA synthase activity was significantly reduced in both whole bone marrow and purified erythroblasts from patients with the anaemia of RA. Erythrocyte protoporphyrin levels were raised in nine of 12 patients tested while ferrochelatase activity was normal. CONCLUSION--These abnormalities provide absolute evidence of abnormal erythroblast haem biosynthesis and iron metabolism in the anaemia of RA and most likely reflect decreased ALA synthase mRNA translation and some abnormality of erythroblast iron transport. Further studies using highly purified erythroblast populations will attempt to identify the causal factors leading to this abnormal erythroblast metabolism.